1997
DOI: 10.1113/jphysiol.1997.sp021967
|View full text |Cite
|
Sign up to set email alerts
|

Is resting state HCO3‐ secretion in frog gastric fundus mucosa mediated by apical Cl(‐)‐HCO3‐ exchange?

Abstract: 1. We have tested the widely accepted hypothesis that resting-state bicarbonate secretion of gastric fundus mucosa is mediated by Cl--HCO3-exchange in the apical membrane of surface epithelial cells (SECs). To this end, SECs of isolated fundus mucosa of Rana esculenta were punctured with double-barrelled microelectrodes to measure intracellular pH (pH1). 2. No significant pH1 changes were observed in response to changing luminal HC03-and/or Clconcentrations. The change in pHi (ApHi) in response to luminal chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…In addition, the predicted increased secretion of carboxylates and, more importantly, of HCO 3 − is expected to counteract, together with bacterial urease, the acidification of the mucous layer due to proton diffusion from the stomach lumen, or to alter acid secretion by oxyntic cells (Debellis et al ., 1998). A leak of the alkaline anion HCO 3 − through the apical membrane of gastric superficial epithelia would be a relevant physiological change mediated by VacA, since it has been shown that this membrane is non‐permeable to this ion under physiological conditions (Caroppo et al ., 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the predicted increased secretion of carboxylates and, more importantly, of HCO 3 − is expected to counteract, together with bacterial urease, the acidification of the mucous layer due to proton diffusion from the stomach lumen, or to alter acid secretion by oxyntic cells (Debellis et al ., 1998). A leak of the alkaline anion HCO 3 − through the apical membrane of gastric superficial epithelia would be a relevant physiological change mediated by VacA, since it has been shown that this membrane is non‐permeable to this ion under physiological conditions (Caroppo et al ., 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, according to previous studies, alkaline secretion seems to originate not only from the SECs (22,54) by mechanisms that are not fully understood (6) but also from the OCs (11,17). The fact that pH gl , either at rest or after stimulation with histamine, did not change in response to the toxin clearly precludes any short-term involvement of these cells in the change in ASR.…”
Section: Discussionmentioning
confidence: 89%
“…However, due to the very short life span of NHE1-and NBCe1-deficient mice, studies measuring their gastric HCO 3 ) secretory rates, even if they would be performed, may be fraught with experimental shortcomings. In addition to measurements of base secretion from the gland depth , Caroppo et al 1997), a number of transporters are expressed in the cells deep in the glands that are involved in fluid movement, but have not been found important for acid secretion (Fujita et al 1999, McDaniel & Lytle 1999, Wang et al 2000, McDaniel et al 2005, Bajwa et al 2009). Several lines of evidence suggest that cells at the base of the glands may also be involved in anion, fluid and possibly HCO 3 ) secretion.…”
Section: Have Measured Hcomentioning
confidence: 99%
“…Several lines of evidence suggest that cells at the base of the glands may also be involved in anion, fluid and possibly HCO 3 ) secretion. In addition to measurements of base secretion from the gland depth , Caroppo et al 1997), a number of transporters are expressed in the cells deep in the glands that are involved in fluid movement, but have not been found important for acid secretion (Fujita et al 1999, McDaniel & Lytle 1999, Wang et al 2000, McDaniel et al 2005, Bajwa et al 2009). However, as the cellular origin of this base secretion is not well defined, the basolateral HCO 3 ) supply pathways remain to be defined.…”
Section: Hco 3 ) Secretion In the Stomachmentioning
confidence: 99%